Impacts of Biomass Burning in the Atmosphere of the Southeastern Region of Brazil Using Remote Sensing Systems - Lopes, F. J. S.; Mariano, G. L.; Landulfo, E.; Mariano, E. V. C. (IntechOpen, 2012)
None